Bacterial hemerythrin domain-containing oxygen and redox sensors: Versatile roles for oxygen and redox signaling - Kitanishi, Kenichi (Frontiers in Molecular Biosciences, 2022)
Hemerythrin is an oxygen-binding protein originally found in certain marine invertebrates. Oxygen reversibly binds at its non-heme diiron center, which consists of two oxo-bridged iron atoms bound to a characteristic conserved set of five His residues, one Glu residue, and one Asp residue. It was recently discovered that several bacteria utilize hemerythrin as an oxygen- and redox-sensing domain in responding to changes in cellular oxygen concentration or redox status, and immediately adapt to these environmental changes in order to maintain important physiological processes, including chemotaxis and c-di-GMP synthesis and degradation. This Mini Review focuses on the recent progress made on structural and functional aspects of these emerging bacterial hemerythrin domain-containing sensor proteins, revealing characteristic features of this family of proteins.